Skenario Pembelajaran dengan Ular Tangga untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa di Kelas VII MTsN 2 Aceh Timur - Zaratuzar (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This study aims to enhance the engagement and learning outcomes of 7th-grade students at MTsN 2 Aceh Timur through the implementation of a learning scenario based on the